An investigation of the Ni/carbonate interfaces on dual function materials in integrated CO2 capture and utilisation cycles - Wu, Xianyue; Chang, Ribooga; Tan, Mingwu; Tao, Longgang; Fan, Qianwenhao; Hu, Xiaochun; Tan, Hui Ling; Åhlén, Michelle; Cheung, Ocean; Liu, Wen (Applied catalysis. B, Environmental, 2023)
CO2 capture and utilisation (CCU) is a promising strategy to effectively mitigate the adverse greenhouse effects caused by CO2 emissions at an industrial scale. Through a process intensification strategy known as integrated CO2 capture and utilisation (ICCU), CO2 capture and catalytic CO2 conversion can be achieved in a single process with the use of dual function materials (DFMs), which are both CO2 sorbents and CO2 conversion catalysts. Given the significantly different operating conditions of ICCU from conventional catalytic CO2 hydrogenation, the catalytic mechanism of DFMs, especially during CO2 hydrogenation, needs to be thoroughly investigated. In this study, the relationship between the nature of the Ni/carbonate interfaces and the performance of Ni-based DFMs over ICCU cycles is systematically investigated. A series of Ni/alkaline earth carbonate DFMs were synthesised with varying Ca:Mg ratios to simulate different metal-carbonate model interfaces. At 400 °C, CH4 formation with nearly 100% CH4 selectivity was achieved on Ni/CaCO3 over 15 ICCU cycles. In general, Ni/CaCO3 interfaces correspond to higher CO2 conversion and higher CH4 selectivity than Ni/MgCO3 interfaces. Such trend may be attributed to the higher surface basicity of CaO and the higher thermal stability of CaCO3. As a consequence, the hydrogenation of the Ni/CaCO3 interface proceed via the formate pathway, in which carbonates are consecutively converted to surface formates, methoxyl, methyl species and eventually desorb as methane. This reaction model is applicable to the hydrogenation of both surface carbonate and bulk carbonates, although the former proceeds with much faster kinetics. On the weakly alkaline Ni/MgCO3 interface, MgCO3 preferentially decomposes to form gaseous CO2, which is subsequently hydrogenated via the reverse-water-gas-shift pathway, with CO as the key reaction intermediate. Interestingly, in situ infrared spectroscopy shows similar surface significant species during the direct hydrogenation of DFMs and during the conventional catalytic hydrogenation of molecular CO2, suggesting that the catalytic mechanisms during the two operating regimes are highly correlated. [Display omitted] •Novel Ni/carbonate dual function materials for CO2 capture and hydrogenation.•Different hydrogenation behaviour and pathway on Ni/CaCO3 and Ni/MgCO3 interfaces.•Two reaction regimes proposed during hydrogenation of Ni/CaCO3.•Suitable basic sites and metal-support interaction favours the hydrogenation.•Correlation between ICCU cycles and those of conventional CO2 hydrogenation.